On a collection of jumping spiders (Araneae: Salticidae) from the Shendurney Wildlife Sanctuary, India - Asima, Ashraf; Caleb, John T.D.; Prasad, Gopal (European Journal of Taxonomy, 2024)
Two new species, Habrocestum sahyadri sp. nov., and Irura shendurney sp. nov. are described from the Shendurney Wildlife Sanctuary, Kerala. The unknown female of Habrocestum kerala Asima, Caleb, Babu #38; Prasad, 2022 is described and three other species: Gelotia lanka Wijesinghe, 1991, Phintella accentifera (Simon, 1901) and Vailimia jharbari Basumatary, Caleb #38; Das, 2020 are recorded from the locality. Detailed descriptions, diagnosis and illustrations of the species are provided.